Kosijeva hiša v kritični podobi vzhodnoslovenskega hišnega tipa - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 1998)
The article brings a survey of the structure of peasant houses and their interrelationship with complex social and cultural factors. The main historical types of houses are: the house of the feudal age or of common system of a three-field crop rotation with fallow land; the house of agrarian technical revolution; the house of industrial society. It is from this point of view that the article treats the historical significance of two-cell dimnica, erected in Mekotnjak in the south of Slovenske Gorice in the second decade of the 19th century.
Keywords: kmečke hiše; stanovanjska arhitektura; zgodovinski pregledi; ethnology; etnologija; 19. st.; Slovenske Gorice; kmečka arhitektura